The Effect of Conventional and Islamic Microfinance on Poverty Alleviation in Bangladesh - Uddin, Nazim; Benabderrahmane, Omar (Milev Journal of Research and Studies, 2019)
Our study evaluated and examined the availability of credit services and outreach as well as propose better effect microfinance services in Bangladesh. The establishment of MFIs in Bangladesh is the result of multiple initiatives by successive government authorities. More recently, microfinance has become a system to address the challenge of poverty, and the past decade has seen a remarkable contribution from MFIs in different parts of the world. Our study used a sample of 400 Islamic and conventional microfinance clients through a simple random sampling technique. In analysing the descriptive data statistics, Pearson Moment correlations, Multiple Regression Analysis (MRA) and parametric tests such as independent t-test and ANOVA were used. The study concluded that the credit facilities are available and accessible in the microfinance institutions irrespective of gender, type of business engaged by the client and the community he/she belongs.